Efficacy of Validamycin at different crop stages against sheath blight of rice - BHUNESHWAR PRATAP SINGH, RAMJI SINGH and (Indian Phytopathology, 2009)
Fourteen different combinations of Validamycin 3L @ 0.1% were applied at different crop growth stages viz. seed, seedling, tillering and symptoms initiation stage, to test their efficacy against sheath blight of rice in field condition and compared with one application of Carbendazim @ 0.1% as standard check. Out of these, Carbendazim was found to be best in reducing the sheath blight severity. However, four application of Validamycin @ 0.1% at four crop stages i.e. seed, seedling, tillering and symptoms initiation, was also found to be equally effective in reducing the disease severity. Two application of Validamycin, i.e. at tillering and symptoms initiation stage also resulted in quite high level of reduction in disease severity. One application of Carbendazim 0.1% and four application of Validamycin 3L @ 0.1% were equally effective in enhancing the rice grain yield also. Application of Validamycin at tillering stage of rice crop seems to have a positive effect in enhancing the efficacy of Validamycin.